PERANCANGAN ENTERPRISE ARCHITECTURE MENGGUNAKAN KERANGKA KERJA ZACHMAN PADA PERUSAHAAN DISTRIBUSI - Johanes Fernandes Andry; Frian Debby; Jodie Darmawan Wijaya; Julia Gunadi (Jurnal Teknologi, 2023)
The implementation of information systems must be equal with company's purpose, because at this business era it is an important thing to be paid more attention to by agencies, because the realization of an effective, efficient and accountable information system will certainly help companies to excel in the competition. PT. Anugerah Familindo Lestari is an industry whose business activity is distributing skin and hair care products, the products distributed by this company already have well-known brands and are believed to have the best formulas. This company already has good governance, but of course the company's problems cannot be said to be finished because the information system within the company is still not used optimally, therefore the company needs to do an Enterprise Architecture that can provide clear direction about data, information and all technology that is needed. There is also a thinking tool that is used to discuss problems in system development, the thinking tool in question is the Zachman Framework, this framework helps map and model the IS and IT architecture within the company to be investigated from various perspectives. This research was conducted using the EAP method with the Zachman framework in the form of initialization and planning, business modeling, analysis of current systems, data architecture, applications and technology and implementation plans, then the authors get the results in the scheme of a blueprint which I hope can be a picture that helps companies to realize the system. information in harmony with the enterprise's vision and mission in the future.